Subjective Cognitive Fatigue in Multiple Sclerosis Depends on Task Length - Sandry, Joshua; Genova, Helen M.; Dobryakova, Ekaterina; DeLuca, John; Wylie, Glenn (Frontiers in Neurology, 2014)
Objective: The objective of this paper is to investigate the interrelationship between subjective and objective cognitive fatigue, information processing domain (processing speed vs. working memory), cognitive load (high vs low), and time on task in Multiple Sclerosis (MS). Methods: 32 MS participants and 24 healthy controls completed experimental tasks in both the processing speed and working memory domains with different levels of cognitive load. Subjective cognitive fatigue was measured using a visual analogue scale (VAS) at baseline and at multiple time points throughout the experiment. Results. A mixed model ANOVA revealed that subjective cognitive fatigue was higher for the processing speed task, increased across time, and was higher in the MS group. These findings were qualified by an interaction demonstrating that the MS group showed a steeper increase in subjective cognitive fatigue over time than the healthy control group. Subjective and objective (i.e., performance) cognitive fatigue were not correlated. Conclusions: In this study, subjective and objective cognitive fatigue appear to be independent and cognitive fatigue does not depend on cognitive load. Subjective cognitive fatigue increased with time on task and subjective cognitive fatigue increased more steeply for the MS group. These data suggest that cognitive fatigue in MS is a function of time, that is, the longer participants were engaged in a cognitive task, the more likely it was for them to report increases in cognitive fatigue.